2014
DOI: 10.1097/nmd.0000000000000100
|View full text |Cite
|
Sign up to set email alerts
|

Risk Taking in Adolescents With Attention Deficit Hyperactivity Disorder on a Probabilistic Choice Task

Abstract: Risk taking is commonly attributed to individuals with attention deficit hyperactivity disorder (ADHD). This study investigated whether adolescents with ADHD would choose to take greater risks on a probabilistic task in which contingencies are explicitly presented. Adolescents with and without ADHD, aged 13 to 18 years, performed a modified version of the Cambridge Gambling Task. The subjects with ADHD risked smaller sums and chose the unfavorable outcomes more frequently than did the controls but had the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
0
7
0
12
Order By: Relevance
“…Interestingly, patients with dorsolateral and dorsomedial PFC lesions exhibited risk-preference choices in the IGT but not the CGT (Manes et al, 2002), suggesting task differentiation in assessing decision-making under risk. While there are some reports that children with ADHD exhibited reduced risk-taking in the CGT (Kroyzer et al, 2014), other findings demonstrated that children with ADHD exhibited increased risk-preference during CGT performance, which as Table 1 Comparison between some available decision-making tasks including the rodent decision-making task (RDT), risky gambling task (RGT), and Iowa Gambling Task (IGT Amphetamine reduces preference for risky reward in rats and mice (Zeeb et al, 2010;van Enkhuizen et al, 2013) Probabilistic learning Human, rat, mouse 'Correct'/1 pellet No reward Amphetamine enhances learning by increasing win-stay strategies ameliorated with methylphenidate treatment (DeVito et al, 2008). Hence, the CGT was sensitive to deficits in medication effects in children with ADHD.…”
Section: Other Methods For Assessing Flexible Decision-making Across mentioning
confidence: 94%
“…Interestingly, patients with dorsolateral and dorsomedial PFC lesions exhibited risk-preference choices in the IGT but not the CGT (Manes et al, 2002), suggesting task differentiation in assessing decision-making under risk. While there are some reports that children with ADHD exhibited reduced risk-taking in the CGT (Kroyzer et al, 2014), other findings demonstrated that children with ADHD exhibited increased risk-preference during CGT performance, which as Table 1 Comparison between some available decision-making tasks including the rodent decision-making task (RDT), risky gambling task (RGT), and Iowa Gambling Task (IGT Amphetamine reduces preference for risky reward in rats and mice (Zeeb et al, 2010;van Enkhuizen et al, 2013) Probabilistic learning Human, rat, mouse 'Correct'/1 pellet No reward Amphetamine enhances learning by increasing win-stay strategies ameliorated with methylphenidate treatment (DeVito et al, 2008). Hence, the CGT was sensitive to deficits in medication effects in children with ADHD.…”
Section: Other Methods For Assessing Flexible Decision-making Across mentioning
confidence: 94%
“…En sentido contrario, el 75% (6 de 8) de los estudios que trabajaron con muestras mixtas de niños y de adolescentes no encontraron diferencias en las medias de los desempeños de ambos grupos (Hovik et al, 2015;Lambek et al, 2011;Masunami et al, 2009;Scheres et al, 2006;Skogli et al, 2014;Skogli et al, 2013). Y la totalidad de los estudios (3) que analizaron sólo el desempeño en adolescentes (Kroyzer et al, 2014;Pollak y Shoham, 2015;Toplak et al, 2005), encontraron evidencias de un desempeño inferior de los jóvenes con TDAH. Los resultados respecto a lo que sucede con los adolescentes son consistentes con los estudios de Bernal, Montaña, Acosta y Rojas (2015), que describen que a partir de los 14 años, a pesar de los avances en el funcionamiento cognitivo, no se observa una mejora gradual en el desempeño en la toma de decisiones, posiblemente debido a un aumento de la búsqueda de sensaciones, a la adopción de comportamientos de riesgo y a la tendencia a alejarse de la norma, afectando el proceso de TD (Reyna y Farley, 2006).…”
Section: Discussionunclassified
“…Otro estudio encontró que el grupo TDAH con comorbilidad con un trastorno negativista desafi ante (TND) asume más riesgos y parece ser más sensible al castigo (Humphreys y Lee, 2011). Los demás estudios que consideraron las comorbilidades, no encontraron diferencias en los niños TDAH con y sin comorbilidad (Antonini et al, 2015;Kroyzer et al, 2014;Lambek et al, 2011). Además, es importante destacar que los estudios que encontraron diferencias signifi cativas en tareas de toma de decisiones, no controlaron la variable comorbilidad, lo cual, considerando los efectos de la presencia de comorbilidades con algunos trastornos, podría conducir a resultados o conclusiones erróneas.…”
Section: Discussionunclassified
“…Las investigaciones sobre la TD en niños y adolescentes con TDAH reportan resultados controvertidos (Rubiales, Urquijo, Said, & Macbeth, 2017). Algunos estudios aportan evidencias de que parecerían más propensos a arriesgarse o a tomar decisiones desfavorables (Drechsler, Rizzo, & Steinhausen, 2010;Kroyzer, Gross-Tsur, & Pollak, 2014;Patros et al, 2015). En esta línea, el modelo dual de Sonuga- sostiene que las personas con TDAH presentan una alteración en los circuitos de recompensa que provoca que la señal de recompensa demorada no sea detectada, por lo cual prefieren recompensas inmediatas aunque pequeñas, antes que recompensas mayores pero demoradas en el tiempo .…”
Section: Palabras Claveunclassified
“…Los estudios de TD en población infanto-juvenil con TDAH no siempre han analizado el desempeño de niños y adolescentes como grupos etarios diferenciados Lambek et al, 2011;Masunami, Okazaki, & Maekawa, 2009;Skogli et al, 2014;. Sin embargo, los estudios que analizaron el desempeño en adolescentes exclusivamente (Kroyzer et al, 2014;Pollak, & Shoham, 2015;Toplak, Jain, & Tannok, 2005), encontraron evidencias de un desempeño inferior de los jóvenes con TDAH. En este sentido, Bernal, Montaña, Acosta y Rojas (2015), describen que en los adolescentes con TDAH no se observa una mejora gradual en el desempeño de la TD posiblemente debido a un aumento de la búsqueda de sensaciones y a la tendencia a alejarse de la norma y sobreestimar los peligros, lo cual se ve reflejado en la adopción de comportamientos de riesgo (Reyna, & Farley, 2006).…”
Section: Palabras Claveunclassified